National and patriatic upbringing as a general demand and challeng of present days - Halyna Diakiv-Mykhayliuk (Vasyl Stefanyk Precarpathian National University, 2018)
The article sets out to establish the importance of national and patriotic upbringing of children and young people on present day Ukraine. It defines structural components of civic and patriotic upbringing, dependency of moral and civic relations and integral qualities of moral and civic culture of a personality. Key words: national and patriotic upbringing of children and young people, moral and civic culture of a personality, biuniqueness dependency of moral and civic relations and integrative qualities of moral and civic culture.